Lagos urbanos: importancia, dinamismo y multiplicidad de usos: el caso del lago Villa Dalcar (Córdoba, Argentina) - Mancini, M. (2012)
Urban lakes are environments with structural and functional features quite different from common lakes. This study aims to present the main results related to the environmental status of Villa Dalcar lake (33°06’25”S, 64°22’31”W, 7 ha), located in the city of Río Cuarto (Córdoba). In this lake, diverse activities as swimming, boating (including motorboat competitions), recreational and for human consumption fishing, removal of bait fish, research and teaching are usually performed. The lake also provides habitat for at least 16 fish species and other communities. However, there has been a significant conflict about the use of water, landscape contamination, fish mortality and different expressions of the trophic state, which was manifested by periods of clear and turbid waters. Different management measures were implemented to control aquatic macrophytes, such as mechanical removal, biomanipulation with fish using Ctenopharyngodon idella and dredging. The results have been variable depending on: the abundance of cyprinids, the activities developed in the basin and the fluctuations in water volume. The lake is a challenge as far as handling is concerned and the latter depends on a number of environmental, social and even political factors.